Por um Pacto Verde Mercosulino: uma proposta a partir da experiência europeia - Silva, Mariela Mendes da (Universidade do Vale do Rio dos Sinos, 2023)
The objective of this master's degree thesis is to analyze the implications of the reorganization of the European society for the confrontation of climatic changes and its implications for the process of commercial integration with MERCOSUR. Additionally, it is assessed the relevance of a Green Pact in MERCOSUR in the context of climatic changes and bi-regional integration with developed regions. In view of the aspirations of commercial integration between MERCOSUR and the European Union and the role of the environmental agenda in this process, the following research problem was formulated: What is the relevance of the coordination of regional environmental policies in MERCOSUR, which contemplate local specificities and the global expectations of facing climatic changes in the region, for the promotion of intra-regional integration and with European Union? The hypothesis of the study indicates that the progress in the construction and implementation of a regional environmental agenda in MERCOSUR, conceived in the light of local environmental challenges, the Sustainable Development Goals, the goals of the Paris Agreement and the guidelines and goals of the European Ecological Pact, in what could be consolidated as a MERCOSUR Green Pact, it would contribute to the consolidation of the regional integration process and to the implementation of the Free Trade Agreement with the European Union. Therefore, the coordination of environmental policies in MERCOSUR is fundamental not only for the progress of integration in the region and to make the aforementioned Agreement viable, but also to reduce climatic changes and their impacts on the Planet. To test the hypothesis of the study qualitative methodology was used, with a deductive, normative-descriptive and comparative approach. The research technique was bibliographic. The results found partially confirm this hypothesis. It was demonstrated that the implementation of an environmental agenda coordinated and effectively committed to confronting climate change in MERCOSUR would favor the materialization of the ongoing integration process, helping the ratification and validity of the EU-MERCOSUR agreement. In addition, it is clear that the progress of the negotiations of the Agreement occurred simultaneously with a series of demonstrations contrary to its effectiveness, by European States, due to the environmental agenda and mitigation of climatic changes in MERCOSUR countries being charged with contradictions. This is especially relevant with regard to the issue of deforestation and change in land use and the review of Brazil's goals in the Paris Agreement. Therefore, the consolidation of a MERCOSUR Green Pact, contemplating the binding commitment with the fulfillment of the goals established in the Paris Agreement; in addition to the standardization of the NDC of the Member States of MERCOSUR, in order to comply with what was established by virtue of that Agreement; as well as a common system for monitoring deforestation and emissions in agriculture in the respective territory, prioritizing economic growth with zero net emissions of greenhouse gases by 2050, in addition to meeting climate demands, would favor the implementation of the biregional integration process.

El objetivo de esta tesina es analizar las implicaciones de la reorganización de la sociedad europea para enfrentar el cambio climático, subrayada en el Pacto Ecológico Europeo, para el proceso de integración comercial con el MERCOSUR, a la luz de la necesidad de se proponer un Pacto Verde para el MERCOSUR. De acuerdo con las intenciones de integración comercial del MERCOSUR con la Unión Europea y el papel de la agenda ambiental en este proceso, se formuló el siguiente problema: ¿Cuál es la relevancia de coordinar políticas ambientales regionales, que incluyan especificidades locales y expectativas globales de combate al cambio climático en el MERCOSUR, para la promoción de la integración regional dentro del bloque y con los países de la Unión Europea? La hipótesis de trabajo es que el avance en la construcción e implementación de una agenda ambiental regional dentro del MERCOSUR, concebida a la luz de los desafíos ambientales locales, los Objetivos de Desarrollo Sostenible, las metas del Acuerdo de París y los lineamientos y metas del Pacto Ecológico Europeo, en lo que podría consolidarse como un Pacto Verde del Mercosur, contribuiría a la consolidación del proceso de integración regional y con la posible entrada en vigor del Tratado de Libre Comercio entre el MERCOSUR y la Unión Europea. Por lo tanto, la coordinación de las políticas ambientales en el MERCOSUR es de fundamental importancia, no sólo para el avance de la integración en la región y para permitir la entrada en vigencia del mencionado Acuerdo, sino también para reducir el impacto que el cambio climático viene causando en el Planeta. Para verificar la veracidad de la hipótesis y responder al problema de investigación, la metodología de trabajo será de carácter cualitativo, con enfoque deductivo, normativo-descriptivo y comparativo y la técnica de investigación será de carácter bibliográfico y documental. Los resultados obtenidos, en definitiva, confirman parcialmente la hipótesis, en el sentido de que la implementación de una agenda ambiental coordinada y efectivamente comprometida con el abordaje del cambio climático dentro del MERCOSUR favorecería la materialización del proceso de integración en curso, contribuyendo a la ratificación y vigencia del Acuerdo MERCOSUR – Unión Europea. Además, es claro que el avance de las negociaciones del citado Acuerdo se dio en paralelo con una serie de manifestaciones contra su implementación, por parte de los Estados europeos, debido a que la agenda ambiental y de mitigación del cambio climático de los países del MERCOSUR está cargada de contradicciones, especialmente en lo que respecta al tema de la deforestación y el cambio de uso del suelo y la revisión de las metas de Brasil en el Acuerdo de París. Por lo tanto, la consolidación de un Pacto Verde del MERCOSUR, que contemple el compromiso vinculante con el cumplimiento de las metas establecidas en el Acuerdo de París; además de la estandarización de las NDC de los Estados Partes del MERCOSUR, a fin de dar cumplimiento a lo establecido en virtud de dicho Acuerdo; así como un sistema común para monitorear la deforestación y las emisiones en la agricultura en el respectivo territorio y priorizar el crecimiento económico sin emisiones netas de gases de efecto invernadero al 2050, además de atender a las demandas climáticas, favorecería la implementación del proceso de integración birregional.
Keywords: MERCOSUL; União Europeia; Acordo de Livre Comércio; Mudanças climáticas; Pacto Verde Mercosulino; MERCOSUR; European Union; Free Trade Agreement; Climate changes; MERCOSUR Green Pact; Unión Europea; Acuerdo de Libre Comercio; Cambios climáticos; Pacto Verde Mercosureño; ACCNPQ::Ciências Sociais Aplicadas::Direito